Relevansi Pendidikan Pancasila Dalam Menghadapi Tantangan Globalisasi - Erfina Erfina; Kadek Vina Dwiyanti; Zainudin Hasan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article discusses the relevance of Pancasila education in facing the increasingly complex challenges of globalization. Pancasila, as the ideology and foundation of the Indonesian state, plays a strategic role in shaping the moral character and national identity of the Indonesian people. Through Pancasila education, young generations are expected to preserve national values amid the positive and negative impacts of globalization. This study employs a normative method with a literature- based approach, analyzing various academic sources related to the significance of Pancasila as a guiding philosophy for the nation. The results of this study indicate that Pancasila education is essential in instilling moral values, strengthening national identity, and serving as a defense against foreign ideologies that may weaken the nation’s character. Strengthening Pancasila education at all levels of education is crucial in preparing the Indonesian nation to compete globally while maintaining its noble values.